(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Establishment of the identity of an individual from dismembered remains or skeletal remains is a common problem encountered by the Forensic Pathologist and can be a challenging task. In addition to age and sex, stature is an anthropological parameter that is indispensable in establishing the identity of an individual. In the present study, we have analyzed the relationship between stature and percutaneous Tibial lengths (PCTL) and derived a regression equation for a specific population. The parameters namely, the stature and percutaneous Tibial lengths (PCTL) of both lower limbs were measured in 115 females belonging to Tamil population and recorded. The subjects were in the age group of 21-30 years. Analysis of the results involved the use of the Pearson’s correlation to derive the relationship between the parameters and establish the dependence of the stature on the length of the left and right Tibia respectively in the study subjects. The results from this present study attest to the utility of the percutaneous Tibial lengths (PCTL) in determination of the stature in females belonging to the Tamil population.